2021
DOI: 10.3390/buildings11030126
|View full text |Cite
|
Sign up to set email alerts
|

Integration of BIM and Immersive Technologies for AEC: A Scientometric-SWOT Analysis and Critical Content Review

Abstract: With the outset of Industrial Revolution 4.0 (IR 4.0), every sector is escalating to get enrichment out of it, whether they are research- or industry-oriented. The Architecture Engineering and Construction (AEC) industry lags a bit in adopting it because of its multi-faceted dependencies and unique nature of work. Despite this, a trend has been seen recently to hone the IR 4.0 multitudes in the AEC industry. The upsurge has been seen in the usage of Immersive Technologies (ImTs) as one of the disruptive techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 185 publications
(114 reference statements)
0
52
0
2
Order By: Relevance
“…Addressing the limitations may facilitate the MRDT adoption process. Khan, Sepasgozar et al (2021) discussed the advantages, benefits and threats of immersive technologies. They conclude that the design sector benefitted most from the immersive technologies and presented more used cases and suggested that this type of technologies should be utilised in health/safety, facility/management and education/training sectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing the limitations may facilitate the MRDT adoption process. Khan, Sepasgozar et al (2021) discussed the advantages, benefits and threats of immersive technologies. They conclude that the design sector benefitted most from the immersive technologies and presented more used cases and suggested that this type of technologies should be utilised in health/safety, facility/management and education/training sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Low field of view (Borisov et al, 2018) Health and safety issues (Cai et al, 2015;Borisov et al, 2018;Wilson et al, 2020) Expensive hardware (Cai et al, 2015), (Alaiad and Zhou, 2017;Pal et al, 2018) Large space requirement (Lee et al, 2012) Security and privacy issues (Cai et al, 2015;Borisov et al, 2018;Wilson et al, 2020) High training cost (Khan et al, 2021) Completeness and accuracy of content offering (Cai et al, 2015) Lack of knowledge (Cai et al, 2015;Borisov et al, 2018;Wilson et al, 2020); Lack of trained workforce (Abrahamse and Lotriet, 2012) High processing requirements (Cai et al, 2015) Time consuming (Chang and Yang, 2010) Isolation caused by HMDs (Alaiad and Zhou, 2017) Interoperability of tools (Borisov et al, 2018;Abrahamse and Lotriet, 2012;Catal et al, 2019) Limited sample size for evaluating the MRDT from users' perspective (Alaiad and Zhou, 2017;Cai et al, 2015;Catal et al, 2019) Compatibility of system (Borisov et al, 2018;Abrahamse and Lotriet, 2012;Atwal et al, 2014) Lack of in-depth data (Borisov et al, 2018) Specific location or situation (Abrahamse andLotriet, 2012, (Cai et al, 2015;Borisov et al, 2018;…”
Section: Technical Limitations Social Limitations Economic Limitationsmentioning
confidence: 99%
“…The number of scholarly papers published on DT in Scopus also shows that academia and practitioner attention has risen, with a large increase in the number of scholarly papers indexed in Scopus and Google search in recent years (1536 in 2020). In order to learn from the VR literature, keywords suggested by Khan, et al [65] were used to identify themes covered previously. Figure 5 shows how the literature is fragmented and that many countries have contributed to developing virtual applications.…”
Section: Scientometric Analysis and Trendsmentioning
confidence: 99%
“…Figure 5a shows 12 main themes of VR technologies and their applications in the literature. The search keywords and content review are presented by Khan, Sepasgozar, Liu and Yu [65]. Applications in the VR dataset were mostly used for educational game and training, defect management, and design objectives.…”
Section: Scientometric Analysis and Trendsmentioning
confidence: 99%
See 1 more Smart Citation